From Frame to Framing - Juhani Pallasmaa (Oz, 2000)
A constructivist aesthetic, emphasizing clear articulation of the structural frame, became the architectural ideal for young Finnish architects of my generation in the early 1960s. This architecture developed as an intellectual opposition to the prevailing post-war tradition of neo-functionalist architecture, which had turned excessively pragmatic and unclear in its philosophical foundation.